A discourse analysis of opening and closing speeches by masters of ceremony on reality television shows in American English versus Vietnames - Lê Thị Trung Dung; Hồ Thị Kiều Oanh, Ph.D. (Da Nang : University of Danang, 2013)
Introduction; Literature review and theoretical background; Method and procedure; ...
Includes appendixes and references (p. 119-124).
Master thesis in social sciences and humanities. Field: The English language. Code: 60.22.15.
Keywords: English language; English language -- Speeches